Sarcoptic Mange in Wild Caprinae of the Alps: Could Pathology Help in Filling the Gaps in Knowledge? - Turchetto, Sara; Obber, Federica; Rossi, Luca; D'Amelio, Stefano; Cavallero, Serena; Poli, Alessandro; Parisi, Francesca; Lanfranchi, Paolo; Ferrari, Nicola; Dellamaria, Debora; Citterio, Carlo V. (Frontiers in Veterinary Science, 2020)
Sarcoptic mange represents the most severe disease for wild Caprinae individuals and populations in Europe, rising concerns for both conservation and management of these ungulates. To date, this disease has been investigated in different wild caprine species and under many different perspectives including diagnostics, epidemiology, impact on the host populations and genetics of both hosts and parasite, with the aim to disentangle the host-Sarcoptes scabiei relationship. Notwithstanding, uncertainty still remains and basic questions still need an answer. Among these, the effect of immunological responses on mange severity at an individual level, the main drivers in host-parasite interactions for different clinical outcomes and the role of the immune response in determining the shift from epidemic to endemic cycle. A deeper approach to pathology of this disease seems therefore advisable, all the more reason considering that immune response to S. scabiei in wild Caprinae, generally classified as a hypersensitivity, still remains poorly understood. In this paper, we started a journey into the pathological features associated to sarcoptic mange in wildlife, exploring different kinds of hypersensitivity and outcomes, with the final goal to highlight the major drivers in the different responses to this disease at an individual level and propose some key topics for future research, with a particular attention to Alps-dwelling wild caprines.